TOWARD THE CATEGORIZATION OF ONLINE POLITICAL PREJUDICES: THE CASE OF THE NEW BRUNSWICK 2020 PROVINCIAL ELECTION. - McLaughlin, Gilbert (Journal of New Brunswick Studies / Revue d'etudes sur le Nouveau-Brunswick)
This paper is qualitative case study of political prejudices on the internet. Negative social media remarks received by candidates in the 2020 New Brunswick provincial election were analyzed. The paper presents a typology for classifying such comments and offers a model for comprehending online prejudices, employing grounded theory techniques. Analysis of the comments reveals some of the challenges faced by contemporary political figures.